Unravelling the transcriptomic landscape of primary lymphocytic scarring alopecias: systematic review and meta-analysis - Rivera-Ruiz, Irene; Ungar, Benjamin; Dávila-Flores, Viviana; Gay-Mimbrera, Jesús; Gómez-Arias, Pedro J.; Juan-Cencerrado, Miguel; Mochón-Jiménez, Carmen; Parra-Peralbo, Esmeralda; Isla-Tejera, Beatriz; López-Viñau López, Teresa; Guttman-Yassky, Emma; Ruano, Juan (Frontiers in Immunology, 2025)
Primary lymphocytic scarring alopecias (PLSAs)—including frontal fibrosing alopecia (FFA), lichen planopilaris (LPP), and central centrifugal cicatricial alopecia (CCCA)—are chronic inflammatory scalp disorders leading to irreversible follicular destruction. Despite overlapping histopathology, their molecular differences remain poorly defined. We performed the first systematic review and transcriptomic meta-analysis of human scalp biopsies in PLSAs (PROSPERO: CRD42024559969), following PRISMA 2020 guidelines. Of 1,080 records screened, eight studies met inclusion criteria; six were eligible for meta-analysis, and two were qualitatively reviewed. The batch-corrected meta-analysis identified shared and subtype-specific transcriptomic alterations. Common features included Th1/IFNγ and JAK/STAT activation, cytotoxic lymphocyte infiltration, and downregulation of epithelial keratins. FFA and LPP showed strong immune activation, while CCCA exhibited lower inflammation but increased mitochondrial stress, lipid metabolism disruption, and fibroblast-associated remodeling. Protein–protein interaction network analysis revealed convergent and divergent molecular modules spanning immune, fibrotic, metabolic, and epigenetic pathways. LPP was uniquely enriched for gene signatures linked to cardiovascular traits, suggesting novel systemic associations. Drug repurposing analyses identified candidate compounds modulating inflammation and metabolism, some reversing inflammatory signatures in brepocitinib-treated samples. This integrated molecular analysis refines our understanding of PLSA subtypes and proposes candidate biomarkers and therapeutic targets, supporting a shift toward biomarker-driven classification and personalized treatment strategies.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO, identifier CRD42024559969.